WOMEN PERCEPTION REGARDING PAPANICOLAOU TEST: FROM OBSERVATIONTO UNDERSTANDING - Silvia Letícia Oliveira; Ana Carla Hidalgo de Almeida (Universidade Federal do Paraná, 2009)
The uterine cervix cancer is the one that most affects women and each year the number of new casesincrease. This study aimed to evaluate the perception of women about the Pap test. Data collection was developed usingsemi-structured interviews. There were 22 participants which were attended by the mobile unit of a municipality in ParanaState. Data were analyzed through content analysis, and then some categories emerged: the superficiality of knowledgeabout the Pap test of the professional who performs the procedure; the appreciation and recognition of the nurse; and theimportance of information for knowledge construction. According to the results of the study, the interviewed women havea superficial and equivocated understanding about the Papanicolaou test, and want to take the test because of its curativeaspect rather than the preventive aspect; also, the nurse has a key role in creating a link of confidence between the userand the health professional, and that information is very important in the construction of knowledge.